Defective Janus type TMDs two-dimensional material lithium ion battery anode material design method

By designing the lithium-ion battery anode material with defective Janus TMDs two-dimensional materials, optimizing the defective configuration and lithium adsorption configuration, the existing anode materials have small capacity, low charge and discharge rate and poor safety, and achieving high capacity, Fast charging and discharging and good stability effects.

CN119495382APending Publication Date: 2025-02-21CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411513392.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have problems such as small theoretical capacity, low charge and discharge rate and poor safety, and are difficult to meet the requirements of large capacity and high lithium-ion mobility and safety.

Method used

Design and construct lithium-ion battery anode materials with defective Janus TMDs two-dimensional materials, and evaluate the stability and electrochemical properties of the material by optimizing the defective configuration and lithium adsorption configuration.

Benefits of technology

Achieving high theoretical capacity, fast charging and discharge and good thermal stability, it provides a potential high-performance lithium-ion battery anode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495382A_ABST
    Figure CN119495382A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion battery anode materials, in particular to a design method of a lithium ion battery anode material of a defective Janus type TMDs two-dimensional material. The method comprises the following steps: (1) designing and constructing a defect Janus type TMDs two-dimensional material model to obtain a stable defect configuration of the material; (2) designing and constructing a Li adsorption configuration based on the defect Janus type TMDs two-dimensional material with the most stable defect configuration, optimizing the adsorption configuration, calculating the adsorption energy of the Li adsorption configuration, and obtaining stable Li adsorption sites through comparison; (3) evaluating the lithium battery performance of the material; (4) evaluating the stability of the material; and (5) further verifying the mechanism that the material can be used as an anode material. According to the method, the defect structure of the Cr9O9S9 material is designed and constructed, change is carried out on the basis of the defect structure, it is determined that the stable configuration of the series of defect structures is Cr9O11S7, and the lithium battery performance of the defect material Cr9O11S7 is predicted for the first time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion battery anode materials, and in particular to a method for designing lithium ion battery anode materials of defective Janus-type TMDs two-dimensional materials. Background Art

[0002] The type and structure of battery electrode materials are directly related to the capacity of the battery and its service life. At present, research on electrode materials at home and abroad mainly focuses on two aspects: one research direction seeks to further improve commercial electrode materials and their performance. The second project aims to explore and develop new electrode materials. Anode materials have always been considered the core part of lithium-ion batteries, so their performance is directly related to the overall performance of lithium-ion batteries. At present, commercial lithium-ion battery anode materials show many problems, mainly manifested in: First, the theoretical capacity is small. The capacity of commercial LiCoO2 anode materials is about 140mAh / g, while the capacity of graphite cathode materials can reach 330mAh / g, and the anode capacity is only about 50% of the cathode capacity. Second, the charge and discharge rate is low. There are many reasons for the low charge and discharge rate, one of which is that the anode material (such as graphite) has a limited ability to accept lithium ions at high rate current. When the discharge rate is too fast, the excess lithium ions cannot be absorbed by the anode material in time, and may precipitate on the anode surface to form lithium dendrites. The growth of lithium dendrites will destroy the anode structure, resulting in a decrease in battery performance or even short circuit. Third, poor safety. Lithium batteries may cause a series of safety problems under the influence of external environmental factors such as overcharging or discharging, high temperature, collision, extrusion, etc., causing certain losses to people and property. Therefore, the research and development of lithium battery anode materials with large capacity, high lithium ion mobility and good safety is of great practical significance.

[0003] With the continuous research on the energy storage performance of lithium-ion batteries, more and more anode materials have been discovered. Among them, two-dimensional transition metal sulfides (TMDs) occupy a very important position. In recent years, Janus-type two-dimensional transition metal sulfide materials derived from TMDs have continued to emerge, showing excellent physical and chemical properties, and have set off a wave of research. Janus-type TMDs materials have a double-sided asymmetric structure, namely the XMY configuration, where X represents a VIA group element, M represents a transition metal, and Y represents a VIA group element different from X. It is precisely because the atoms on its upper and lower surfaces are different that some unique electronic properties are produced. For example, high ion diffusion rate is conducive to the rapid transmission of lithium ions in the anode material, thereby improving the charge and discharge rate of the battery; good electrochemical stability and reversible lithium ion deintercalation ability enable these materials to achieve long-term charge and discharge cycles, thereby improving the cycle life of the battery; higher theoretical capacity can store more Li ions and increase the energy density of the battery.

[0004] In fact, there are often some defects in both natural crystalline materials and experimentally synthesized crystalline materials. Studies have shown that certain defects can affect the battery performance of anode materials to a certain extent. For example, Fan et al. found that the presence of impurities and defects can increase the lithium storage limit of graphene. Bazant et al. found that surface defects can change thermodynamic properties, increase surface energy, and thus affect alkali metal ion intercalation. This is because the atoms in the defective area are rearranged, resulting in an enhanced binding effect between alkali metal ions and defective materials. Liu et al. found that defect-induced Ti2C monolayers have a significant effect on the adsorption and storage capacity of Li. Summary of the invention

[0005] The present invention aims to provide a design method for a defective Janus-type TMDs two-dimensional material as a lithium-ion battery anode. By designing the defect configuration of the Janus-type TMDs two-dimensional material, the lithium battery performance of the defective material is comprehensively evaluated.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A method for designing a lithium ion battery anode material of a defective Janus-type TMDs two-dimensional material, comprising the following steps:

[0008] The first step is to design and construct the defect configuration of Janus-type TMDs two-dimensional materials, optimize each defect configuration, calculate the defect formation energy of each defect configuration, and compare the structure with the lowest defect formation energy to obtain the most stable defect configuration;

[0009] The second step is to design and construct the Li adsorption configuration based on the defective Janus-type TMDs two-dimensional material with the most stable defect configuration, optimize the adsorption configuration, calculate the adsorption energy of the Li adsorption configuration, and obtain the stable Li adsorption site by comparison;

[0010] The third step is to design and construct a multilayer lithium adsorption configuration based on stable Li adsorption sites, thereby calculating the theoretical capacity and open circuit voltage of the material;

[0011] The fourth step is to evaluate the stability of the material: using molecular dynamics simulation methods, we compared and analyzed the stability changes of defective Janus-type TMDs two-dimensional materials and their stability after lithiation in the temperature range of 300-500K;

[0012] The fifth step is to evaluate the electrochemical performance of the material: using the transition state search method CI-NEB to simulate the diffusion process of lithium ions in the anode material and characterize the charge and discharge rate of the lithium battery;

[0013] The sixth step is to explain the mechanism by which defective Janus-type TMDs two-dimensional materials can be used as anode materials.

[0014] Furthermore, the defect configuration in the first step includes:

[0015] According to the structural characteristics of Janus-type TMDs two-dimensional materials such as atomic types and symmetry, their defect configurations are designed and constructed, including structural models of single vacancy defects, double vacancy defects, single substitutional atomic defects, double substitutional atomic defects, single interstitial defects and double interstitial defects.

[0016] Furthermore, the defect formation energy E f The calculation formula is:

[0017] E f =E defect -E pristine ±∑n i μ i

[0018] Among them, E defect is the total energy of the defect system, E pristine is the total energy of the complete system, n is the number of atoms, μ is the chemical potential of a single defective atom, and i is the type of element.

[0019] Furthermore, the design and construction of the multilayer lithium adsorption configuration in the third step includes the following steps:

[0020] (a) On the upper and lower surfaces of the substrate material, the adsorption energies of all possible adsorption sites are calculated, and the adsorption configuration with the lowest adsorption energy is selected as the first stable configuration of Li; then, the adsorption energies of the remaining possible adsorption sites are calculated, and the adsorption configuration with the lowest adsorption energy is selected as the second stable configuration of Li, and so on, until the upper and lower surfaces of the material are fully adsorbed, that is, the adsorption configuration of double-layer lithium is obtained;

[0021] (b) on the basis of the double-layer lithium adsorption configuration, repeating the process of step (a) until the adsorption energy of Li ions is greater than -1.61 eV (the cohesive energy of crystalline Li), and finally obtaining a multi-layer lithium adsorption configuration;

[0022] Furthermore, the calculation formula of the theoretical capacity C in the third step is:

[0023]

[0024] Where z is the valence of lithium ions, F is the Faraday constant, M is the molar mass of the system, and 3.6 is the unit conversion factor.

[0025] Furthermore, the open circuit voltage V ocv The calculation formula is:

[0026]

[0027] Where e is the elementary charge, which is equal to 1.6×10 -19 C, E defect is the energy of the system before adsorption, E Li is the energy of a single Li, is the total energy of the entire system after the adsorption of n Li atoms, where n is the number of adsorbed Li atoms.

[0028] Furthermore, the fifth step of analyzing the diffusion process of Li ions in the material includes the following steps:

[0029] (a) According to the stability of Li ions on the surface of the substrate material, the two most stable sites are selected as the initial and final positions of Li ion migration;

[0030] (b) Design the migration path between the initial and final positions, interpolate points between the initial and final positions, find the saddle point through transition state calculation using the CI-NEB method, obtain the barrier height, and draw the diffusion barrier diagram of the migration path;

[0031] (c) Based on the diffusion barrier diagram, the optimal migration path of Li ions is determined.

[0032] Furthermore, the calculation formula for the differential charge density in the sixth step is:

[0033] ρ=ρ after -ρ Li -ρ before

[0034] Among them, ρ after and ρ before Respectively represent defective materials Cr9O 11 Charge density of S7 before and after Li adsorption, ρ Li Charge density of a single Li atom.

[0035] Compared with the prior art, the advantages of the present invention are:

[0036] The present invention designs and constructs the defect structure of Cr9O9S9 material, and changes are made on the basis of the defect structure to determine that the stable configuration of the series of defect structures is Cr9O 11 S7, and predicted for the first time the defective material Cr9O 11 The lithium battery performance of S7 mainly includes adsorption energy, theoretical capacity, open circuit voltage, thermal stability and diffusion barrier, etc. It proposes a feasible theoretical scheme for the above-mentioned material as anode material for lithium-ion batteries, and lays a theoretical foundation for the development of new lithium-ion battery anode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1It is a flow chart of the design method of lithium-ion battery anode materials based on defective Janus-type TMDs two-dimensional materials;

[0038] Figure 2 It is Cr9O with optimized structure. 11 Schematic diagram of the top and side views of the upper and lower surfaces of the S7 material;

[0039] Figure 3 A single Li atom is adsorbed on Cr9O 11 Schematic diagram of all possible adsorption sites on the surface of S7 material;

[0040] Figure 4 It is Cr9O 11 Adsorption energy bar graph of Li atoms that can be stably adsorbed in S7 material, where (a) is the adsorption energy bar graph of the O surface that can stably adsorb the site, and (b) is the adsorption energy bar graph of the S surface that can stably adsorb the site;

[0041] Figure 5 is the energy change diagram, where (a) and (b) are Cr9O 11 Energy variation of S7 material at 300-500K. (c) (d) is Cr9O 11 The energy variation of S7 material at 300-500K after adsorbing lithium atoms.

[0042] Figure 6 Schematic diagram of the migration path of Li ions. (a) is a schematic diagram of the migration path of Li ions on the O surface, (b) is a schematic diagram of the migration path of Li ions on the S surface; (c) and (d) are the diffusion barrier diagrams of Li ions on the O surface and S surface respectively;

[0043] Figure 7 It is defective Cr9O 11 Total density of states diagram of S7 before and after adsorption of Li atoms;

[0044] Figure 8 Li atoms are adsorbed on Cr9O 11 Differential charge density plot on S7. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with the examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies realized based on the content of the present invention belong to the scope of the present invention.

[0046] Example

[0047] The present invention provides an application of a defective Janus-type TMDs two-dimensional material in a Li-ion battery. Preferably, the defective configuration of the two-dimensional CrSO material is used as an anode material for a lithium-ion battery.

[0048] A method for designing lithium-ion battery anode materials based on defective Janus-type TMDs two-dimensional materials, as shown in the flow chart Figure 1 As shown, the following steps are included:

[0049] The first step is to design and construct the defect configuration of CrSO material, optimize each defect configuration, calculate its defect formation energy and compare it to obtain the structure with the lowest defect formation energy, which is the most stable defect configuration.

[0050] The second step is to use the defect structure of the most stable CrSO material, Cr9O 11 S7, design and construct Li adsorption configurations, optimize each adsorption configuration, calculate its adsorption energy and compare to obtain stable Li adsorption sites;

[0051] The third step is to design and construct a multilayer lithium adsorption configuration to calculate the theoretical capacity and open circuit voltage of the material;

[0052] The fourth step is to evaluate the stability of the material: using molecular dynamics simulation methods, the stability changes of CrSO materials and their lithiation in the temperature range of 300-500K are compared and analyzed;

[0053] The fifth step is to evaluate the electrochemical performance of the material: using the transition state search method CI-NEB to simulate the diffusion process of lithium ions in the anode material and characterize the charge and discharge rate of the lithium battery;

[0054] The sixth step is to explain the mechanism by which CrSO can be used as anode material: analyzing the electronic structure properties of the material, such as state density, differential charge density, etc.

[0055] In the first step above, the defect configuration includes:

[0056] According to the atomic species, symmetry and other structural characteristics of the two-dimensional CrSO material, the defect configuration of the two-dimensional CrSO material is designed and constructed, including single vacancy defect, double vacancy defect, single substitution atom defect, double substitution atom defect, single interstitial defect and double interstitial defect. After structural optimization based on the above defect configurations and comparison of defect formation energy, the most stable defect configuration is obtained: Cr9O 11 S7, its structure is as follows Figure 2 As shown. Among them, Figure 2 (a) is the S-plane, where two oxygen atoms replace two sulfur atoms. Figure 2(b) is the O surface, the middle layer is the Cr atomic layer, and the black dotted line circle in the figure represents the defect point formed by replacing S atoms with O atoms in the S layer. After structural optimization, the defect material Cr9O 11 The lattice constant of S7 is and O face: Cr-O bond length is S plane: Cr-S bond length is The Cr-O bond length is Based on this stable defect configuration, its potential as anode material for lithium-ion batteries is comprehensively evaluated.

[0057] In the first step above, the defect formation energy E f The calculation formula is as follows:

[0058] E f =E defect -E pristine ±∑n i μ i

[0059] Among them, E defect is the total energy of the defect material, E pristine is the total energy of the complete CrSO material, n is the number of atoms, μ is the chemical potential of the defect atom, and i is the element type. 11 The defect formation energy of S7 is -7.23 eV, which indicates that the formation of this defect is an exothermic reaction. 11 S7 is relatively stable and easy to synthesize.

[0060] In the second step above, the design and construction of the adsorption configuration includes the following steps:

[0061] Defective material Cr9O 11 S7 has asymmetric upper and lower surfaces, the S-face and the O-face. Due to the presence of two oxygen defect sites on the S-face, the number of Li adsorption sites on the S-face is much greater than that on the O-face. Figure 3 (a) shows the Li adsorption sites on the S surface, 1 represents the top site (T site) directly above the defective O atom, 2, 4, and 8 represent the bridge site (B site) where the Cr atom and O / S form a bond, 3 and 7 represent the top site (M site) directly above the Cr atom, 5 represents the top site (T site) directly above the S atom, and 6 and 9 represent the hole site (H site) at the center of the regular hexagon. Figure 3 (b) shows the Li adsorption sites on the O surface, where 1 represents the hole site (H site) at the center of the regular hexagon, 2 represents the top site (M site) directly above the Cr atom, 3 represents the adsorption site (T site) directly above the O atom, and 4 represents the bridge site (B site) where the Cr atom bonds with O / S.

[0062] In the second step above, the defective material Cr9O 11 The adsorption energy of Li on S7 (E ad ) is calculated as follows:

[0063] E ad =(E after -E before -nE Li ) / n

[0064] Among them, E after and E before Defective materials are Cr9O 11 S7 Total energy after and before Li adsorption; E Li is the energy of a single Li atom, and n is the number of adsorbed Li atoms. The smaller the adsorption energy, the greater the defective Cr9O 11 The stronger the interaction between S7 and Li, the stronger the interaction between S7 and Li. After structural optimization, only 5 adsorption configurations are stable. Figure 4 The adsorption energies corresponding to the stable adsorption configurations on the O and S surfaces are given. It can be seen that the adsorption energies of Li on O surfaces 1, 2 and S surfaces 2, 3, 6 are -2.69eV, -2.52eV, -1.21eV, -0.68eV, and -0.57eV, respectively. Therefore, the most stable adsorption position of Li on the O surface is 1 (H position), and the most stable adsorption position on the S surface is 2 (B position). 11 In the S7 structure, the most stable adsorption site is the 1st position (H position) of the O face, which is located at the center of the regular hexagon.

[0065] In the third step above, the design and construction of the multilayer lithium adsorption configuration includes the following steps:

[0066] (a) On the upper and lower surfaces of the substrate material, the adsorption energies of all possible adsorption sites are calculated, and the adsorption configuration with the lowest adsorption energy is selected as the first stable configuration of Li; then, the adsorption energies of the remaining possible adsorption sites are calculated, and the adsorption configuration with the lowest adsorption energy is selected as the second stable configuration of Li, and so on, until the upper and lower surfaces of the material are fully adsorbed, that is, the adsorption configuration of double-layer lithium is obtained;

[0067] (b) On the basis of the double-layer lithium adsorption configuration, the process of step (a) is repeated until the adsorption energy of Li ions is greater than -1.61 eV (the cohesive energy of crystalline Li), and finally a multi-layer lithium adsorption configuration is obtained. 11 S7 can stably adsorb 56 Li atoms, of which the O surface can adsorb multiple layers of lithium, while the S surface can only adsorb 2 lithium atoms at defect sites.

[0068] In the third step above, the theoretical capacity C is calculated as:

[0069]

[0070] Where z is the valence of lithium ions, F is the Faraday constant, M is the molar mass of the system, and 3.6 is the unit conversion factor. 11 The open circuit voltage range of S7 is 0.22~1.2V, which is suitable as anode material for lithium batteries.

[0071] In the third step above, the open circuit voltage V ocv The calculation formula is:

[0072]

[0073] Where e is the elementary charge, which is equal to 1.6×10 -19 C, E defect is the energy of the system before adsorption, E Li is the energy of a single Li, is the total energy of the whole system after adsorbing n Li atoms, where n is the number of adsorbed Li atoms. 11 The theoretical capacity of S7 is 1697mAh / g, far exceeding most anode materials.

[0074] In the fourth step, the stability of the material is evaluated: molecular dynamics simulation is used to compare and analyze the stability changes of defective Janus-type TMDs two-dimensional materials and their lithiation in the temperature range of 300-500K. Figure 5 is the energy change diagram, where (a) and (b) are Cr9O 11 Energy variation of S7 material at 300-500K. (c) (d) is Cr9O 11 The energy variation of S7 material at 300-500K after adsorbing lithium atoms.

[0075] In the fifth step above, the diffusion process of Li ions in the material includes the following steps:

[0076] (a) According to the stability of Li ions on the surface of the substrate material, the two most stable sites are selected as the initial and final positions of Li ion migration;

[0077] (b) Design the migration path between the initial and final positions, interpolate points between the initial and final positions, find the saddle point through transition state calculation using the CI-NEB method, obtain the barrier height, and draw the diffusion barrier diagram of the migration path;

[0078] (c) Based on the diffusion barrier diagram, the optimal migration path of Li ions is determined.

[0079] Figure 6 The Li in defective material Cr9O11 There are two diffusion paths on different surfaces of S7. Among them, the diffusion path on the O surface is HTH, and the diffusion barrier is 0.17eV, which is lower than the diffusion barrier of traditional graphene (0.45eV). The diffusion path on the S surface is BMHB, and the diffusion barrier is 0.75eV. 11 The S-plane Li diffusion barrier of S7 is higher, but since the number of lithium atoms that can be stably adsorbed on the S-plane is small, the effect on the performance of the entire anode material is small. 11 The S7 surface can diffuse quickly, which is beneficial to the charging and discharging rate of lithium batteries.

[0080] In the sixth step above, the calculation method of the differential charge density ρ is as follows:

[0081] ρ=ρ after -ρ Li -ρ before

[0082] Among them, ρ after and ρ before Respectively represent defective materials Cr9O 11 Charge density of S7 before and after Li adsorption, ρ Li Charge density of a single Li atom.

[0083] Figure 7 It is defective Cr9O 11 Total state density diagram of S7 before and after adsorption of Li atoms, Figure 8 Shows defect Cr9O 11 Differential charge density diagram after S7 adsorbs Li atoms; (a) (c) are the top view and side view of the most stable adsorption site of Li atoms on the O surface, and (b) (d) are the top view and side view of the most stable adsorption site of Li atoms on the S surface. Figure 8 Differential charge density distribution diagram in Cr9O 11 S7 is the main charge acceptor, and the dark and light areas represent the charge reduction area and charge accumulation area, respectively. It can be clearly seen from the figure that the charge transfer occurs in the local area around the Li atom. By bader charge analysis, it can be calculated that the Li atom transfers to the defective Cr9O 11 The number of electrons transferred by S7 is 0.92e and 0.91e, indicating that Li and defective Cr9O 11 The O of S7 forms a strong interaction, which further explains the defective material Cr9O 11 Stability of S7 as anode material for lithium-ion batteries.

[0084] In summary, the present invention proposes a design method for a defective Janus-type TMDs two-dimensional material as an anode material for lithium-ion batteries. Based on this design method, a stable defect configuration of the two-dimensional material CrSO, Cr9O 11 S7, evaluated its good lithium battery performance: theoretical capacity 1697mAh / g, open circuit voltage range 0.22~1.2V, good thermal stability (below 500K), diffusion barrier 0.1735eV; at the same time, through the defective material Cr9O 11 The electronic structure analysis of S7 revealed that there was a strong hybridization between the S orbital of Li and the P orbital of O, which made the Li adsorption more stable. The results of large capacity, low diffusion barrier and low open circuit voltage indicate that the defective Cr9O 11 S7 is expected to be a promising anode material for lithium-ion batteries.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for designing anode materials for lithium-ion batteries of defective Janus-type TMDs two-dimensional materials, characterized in that: The following steps are involved: The first step is to design and construct the defect configuration of Janus-type TMDs two-dimensional materials, optimize each defect configuration, calculate the defect formation energy of each defect configuration, and compare the structure with the lowest defect formation energy to obtain the most stable defect configuration; The second step is to design and construct the Li adsorption configuration based on the defective Janus-type TMDs two-dimensional material with the most stable defect configuration, optimize the adsorption configuration, calculate the adsorption energy of the Li adsorption configuration, and obtain the stable Li adsorption site by comparison; The third step is to design and construct a multilayer lithium adsorption configuration based on stable Li adsorption sites, thereby calculating the theoretical capacity and open circuit voltage of the material; The fourth step is to evaluate the stability of the material: using molecular dynamics simulation methods, we compared and analyzed the stability changes of defective Janus-type TMDs two-dimensional materials and their stability after lithiation in the temperature range of 300-500K; The fifth step is to evaluate the electrochemical performance of the material: using the transition state search method CI-NEB to simulate the diffusion process of lithium ions in the anode material and characterize the charge and discharge rate of the lithium battery; The sixth step is to explain the mechanism by which defective Janus-type TMDs two-dimensional materials can be used as anode materials.

2. A method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The defect configuration described in the first step includes: According to the atomic types and symmetry structural characteristics of Janus-type TMDs two-dimensional materials, defect configurations are designed and constructed, including structural models of single vacancy defects, double vacancy defects, single substitutional atomic defects, double substitutional atomic defects, single interstitial defects and double interstitial defects.

3. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The defect formation energy E in the first step f The calculation formula is: AND f =And defect -AND pristine ±∑n i μ i Among them, E defect is the total energy of the defect material, E pristine is the total energy of the complete material, n is the number of atoms, μ is the chemical potential of the defect atom, and i is the element type.

4. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The adsorption energy E in the second step ad Calculation formula: AND ad =And Li_defect -AND defect -∑n Li μ Li Among them, E Li_defect is the total energy of the defect system after Li adsorption, E pristine is the total energy of the defect system, n is the number of Li atoms, μ Li Expressed as the chemical potential of Li atoms.

5. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The design and construction of the multilayer lithium adsorption configuration in the third step includes the following steps: (a) On the upper and lower surfaces of the substrate material, the adsorption energies of all possible adsorption sites are calculated, and the adsorption configuration with the lowest adsorption energy is selected as the first stable configuration of Li; then, the adsorption energies of the remaining possible adsorption sites are calculated, and the adsorption configuration with the lowest adsorption energy is selected as the second stable configuration of Li, and so on, until the upper and lower surfaces of the material are fully adsorbed, that is, the adsorption configuration of double-layer lithium is obtained; (b) On the basis of the double-layer lithium adsorption configuration, the process of step (a) is repeated until the adsorption energy of Li ions is greater than the cohesive energy of crystalline Li, and finally a multi-layer lithium adsorption configuration is obtained.

6. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The calculation formula of the theoretical capacity C in the third step is: Where z is the valence of lithium ions, F is the Faraday constant, M is the molar mass of the system, and 3.6 is the unit conversion factor.

7. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The open circuit voltage V ocv The calculation formula is: Where e is the elementary charge, which is equal to 1.6×10 -19 C, E defect is the energy of the system before adsorption, E Li is the energy of a single Li, is the total energy of the entire system after the adsorption of n Li atoms, where n is the number of adsorbed Li atoms.

8. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The fifth step of analyzing the diffusion process of Li ions in the material includes the following steps: (a) According to the stability of Li ions on the surface of the substrate material, the two most stable sites are selected as the initial and final positions of Li ion migration; (b) Design the migration path between the initial and final positions, interpolate points between the initial and final positions, find the saddle point through transition state calculation using the CI-NEB method, obtain the barrier height, and draw the diffusion barrier diagram of the migration path; (c) Based on the diffusion barrier diagram, the optimal migration path of Li ions is determined.

9. The method for designing a lithium-ion battery anode material of a defective Janus-type TMDs two-dimensional material as claimed in claim 1, characterized in that: The calculation formula for the differential charge density in the sixth step is: p=p after -r Li -r before Among them, ρ after and ρ before Respectively represent defective materials Cr9O 11 Charge density of S7 before and after Li adsorption, ρ Li Charge density of a single Li atom.

10. A storage medium, characterized in that: Instructions executable by a processor are stored thereon, and when the instructions are executed by the processor, the processor executes the method for designing lithium-ion battery anode materials of defective Janus-type TMDs two-dimensional materials as described in any one of claims 1 to 9.